2007
DOI: 10.1159/000107626
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Corticosteroid Therapy for Alopecia Areata: Study of 139 Patients

Abstract: Background/Aim: Recent reports of pulse corticosteroid therapy for alopecia areata (AA) show its efficacy for patients with a history of ≤1 year but not for recalcitrant cases or alopecia totalis/universalis. The purpose of this study was to evaluate the efficacy and safety of pulse corticosteroid therapy for recent-onset AA patients. Method: A total of 139 severe AA patients aged >15 years were included in this study. The duration from the onset of active hair loss was within 12 months for 125 (89.9%) of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
88
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 61 publications
15
88
2
1
Order By: Relevance
“…In our study disease severity was found to predict therapeutic response, as patients with multifocal disease had a higher likelihood to respond to treatment than patients with ophiatic AA, AT or AU. A poor treatment response in patients with the severe variants has also been suggested by previous studies [4,10,15,17,19]. …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In our study disease severity was found to predict therapeutic response, as patients with multifocal disease had a higher likelihood to respond to treatment than patients with ophiatic AA, AT or AU. A poor treatment response in patients with the severe variants has also been suggested by previous studies [4,10,15,17,19]. …”
Section: Discussionsupporting
confidence: 69%
“…In 1975 Burton and Shuster [13] were the first to administer a single 2-gram intravenous methylprednisolone pulse in 22 patients with AA; however, only 3 (14%) had satisfactory hair regrowth. Thereafter, several additional studies showing a beneficial effect of pulse corticosteroids, either intravenous [4,10,14,15,16,17,18,19] or oral [9,20,21,22], were published. Four of these studies [4,14,18,20] concern a pediatric population (a total of 39 patients) (table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 203 patients treated with intralesional steroids, only 6% had significant local side effects. Studies report that combination therapy of oral dexamethasone mini pulse and topical minoxidil lotion is effective on severe recalcitrant AA [11]. These were well tolerated in our patients, only one patient developed side effects with systemic steroids, and one patient developed irritation with topical minoxidil.…”
Section: Discussionsupporting
confidence: 51%
“…Local steroids (topical or intralesional) are effective in treatment of localised AA [10]. Systemic steroids and topical minoxidil lotionare effective in severe disease [11,12].…”
mentioning
confidence: 99%
“…We diagnosed AA by a precedence of typical patchy AA, later progression to alopecia totalis or scalp biopsy findings corresponding to AA. Then, we extracted the cases corresponding to ADTAFS by the following criteria: (1) rapid progression evidenced by an increase in total hair loss of more than 20% over the month prior to the first visit, (2) showing no apparently circumscribed hair loss at the first visit and (3) favorable prognosis evidenced by more than 75% regrowth of alopecia within 9 months after oral or intravenous corticosteroid pulse therapy (oral prednisolone 30 mg/day on 3 consecutive days for 2 weeks × 3 cools or intravenous methylprednisolone 500 mg/day on 3 consecutive days) or application of topical corticosteroid [16]. The age of the ADTAFS patients varied from 15 to 57 years, and the median age was 32.5 years.…”
Section: Methodsmentioning
confidence: 99%